2012
DOI: 10.1590/s1517-83822012000400015
|View full text |Cite
|
Sign up to set email alerts
|

Production of peptide antibiotics by Bacillus sp: GU 057 indigenously isolated from saline soil

Abstract: A total of 112 soil samples were taken from differents areas of district D.I.Khan and Kohat (KPK) Pakistan and screened for production of antibiotics against the Micrococcus luteus and Staphylococcus aureus. Widest zone of inhibition (18mm) was produced by microorganism isolated from saline soil. The strain was later identified as Bacillus GU057 by standard biochemical assays. Maximum activity (18mm inhibition zone) was observed against Staphylococcus aureus after 48 hours of incubation at pH 8 and 4% concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 1 publication
0
21
0
2
Order By: Relevance
“…Bacillus spp. makes antibiotic compound i.e colistin and polymixin, that are effective against Gram-negative bacteria (Amin et al, 2012). A research conducted by Navinchandran et al (2014) revealed that extracellular enzymes that are produces by B. cereus as probiotics (supplemented through shrimp feed) can increase both immunology parameters and growth of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus spp. makes antibiotic compound i.e colistin and polymixin, that are effective against Gram-negative bacteria (Amin et al, 2012). A research conducted by Navinchandran et al (2014) revealed that extracellular enzymes that are produces by B. cereus as probiotics (supplemented through shrimp feed) can increase both immunology parameters and growth of the host.…”
Section: Discussionmentioning
confidence: 99%
“…were transferred. The agar plates were incubated at 37 o C for 24hr and the zones of inhibition around each well were measured [1] Determining the optimal conditions for antibacterial activity of Bacillus spp.…”
Section: Screening Antibacterial Activity Produced By Bacillus Sppmentioning
confidence: 99%
“…The plates were conserved at room temperature for 1hr., and then they were incubated at optimal cultural conditions. After the incubation period, the inhibitory zones (mm) were measured [1] Antibiofilm analysis of the extracts The biofilm inhibition assay was described by [16]. Following incubation for 24hr., the biofilm was allowed to be formed.…”
Section: Applications Of Purified Extracts As Antibacterial Antibiofmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, epibiotic bacteria from marine sponge Petrosia ficiformis (Chelossi et al 2004), bacteria from marine mollusc Anadara broughtani from the sea of Japan (Romanenko et al 2008), marine bacteria from Sydney Harbour (Wilson et al 2010), marine bacteria in biofilms (Wilson et al 2011) and sponge endosymbiotic bacteria at Agatti Island, Lakshadweep Archipelago (Mohan et al 2016), heterotrophic bacteria from Palk Bay sediments (Nithya and Pandian 2010), bacteria isolated from saline soil (Amin et al 2012), and from soil (Abbas et al 2014) also showed antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%